Time‐interval analysis of ductus venosus flow velocity waveforms in twin‐to‐twin transfusion syndrome treated with laser surgery. (7th April 2015) - Tachibana, D.; Glosemeyer, P.; Diehl, W.; Nakagawa, K.; Wada, N.; Kurihara, Y.; Fukui, M.; Koyama, M.; Hecher, K.
ABSTRACT: Objectives: To investigate time‐interval variables of ductus venosus (DV) flow velocity waveforms (FVWs) in twin‐to‐twin transfusion syndrome (TTTS), comparing the results with reference ranges from normal singleton fetuses. The impact of laser surgery and the effect of prognostic factors were also evaluated. Methods: In 107 TTTS cases, DV‐FVWs of both recipients and donors were recorded 1 day before and 2 days after laser therapy. Time intervals for systolic (S) and early diastolic (D) peaks were analyzed retrospectively with regard to acceleration time (acc‐S and acc‐D for S and D, respectively) and deceleration time (dec‐S and dec‐D for S and D, respectively). For each variable, Z ‐scores were calculated with respect to previously reported normal reference ranges. Results: Z ‐scores for all variables showed statistically significant differences from those observed previously in normal fetuses, with the exception of dec‐S of donors. The most striking differences were observed in longer dec‐S of recipients ( P  < 0.001) and longer dec‐D of donors ( P  < 0.001). Laser therapy showed significant impact on dec‐S and acc‐D in recipients and on all variables in donors. Regarding the short‐term prognosis, acc‐S and dec‐S showed significant differences for the prediction of intrauterine fetal demise in donors ( P  = 0.009 and P  = 0.011, respectively). Conclusion: This study demonstrates that time‐interval variables of DV‐FVWs may differentiate the characteristic hemodynamic changes caused by unbalanced blood volume between recipients and donors. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.